2017
DOI: 10.1080/09638288.2017.1370499
|View full text |Cite
|
Sign up to set email alerts
|

Art participation for psychosocial wellbeing during stroke rehabilitation: a feasibility randomised controlled trial

Abstract: Undertaking a RCT of art participation within stroke rehabilitation was feasible. Art participation may enhance self-efficacy and positively influence emotional wellbeing. These should be outcomes in a future definitive trial. A cluster RCT would ensure art groups could be reliably convened. Fewer measures, and better retention strategies are required. Implications for Rehabilitation This feasibility randomised controlled trial (RCT) showed that recruiting and retaining stroke survivors in an RCT of a visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(89 citation statements)
references
References 40 publications
(41 reference statements)
3
82
3
1
Order By: Relevance
“…The majority of people who took part in the HoS groups highly valued them, with many reporting increased confidence both within and outside the groups. The numbers who declined the intervention were similar to those reported in the Morris et al study 47 48. Study retention was good (with follow-up data available for 84% of participants) and high data completion rates (>80% for the candidate primary outcome measures).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The majority of people who took part in the HoS groups highly valued them, with many reporting increased confidence both within and outside the groups. The numbers who declined the intervention were similar to those reported in the Morris et al study 47 48. Study retention was good (with follow-up data available for 84% of participants) and high data completion rates (>80% for the candidate primary outcome measures).…”
Section: Discussionsupporting
confidence: 66%
“…Modifying the description of the HoS intervention, such as referring to it as ‘an opportunity to reconnect with and gain confidence in everyday life’, rather than calling it an arts intervention could be one way to enhance recruitment. Morris et al suggested that provision of taster sessions may be another means of improving study enrolment, 48 although we note a risk of jeopardising equipoise or increasing the likelihood of resentful demoralisation. Additionally, we could extend the eligibility criteria by providing additional support so that those who require support with toileting needs could attend, although this would have cost implications.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations